Antioxidants Effects on Human Sperm Cryopreservation: A Scoping Review (Bangladesh Journal of Medical Science, 2026)
Background Sperm Cryopreservation has become a routinely used procedure in assisted reproductive technology. This procedure keeps sperm preserved for later use for patients who will undergo chemotherapy, have ejaculation problems, and many other medical indications. This procedure allows the patients to preserve their fertility potential for having their offspring in the future by storing the sperm in a very low temperature of liquid nitrogen. However, this technique raises some concerns regarding the reduction in post-thawed quality. This adverse effect is caused by thermal shock, osmotic shock, and oxidative stress during the freezing and thawing process. Among these, oxidative stress is considered the primary factor contributing to the significant decline in post-thawing sperm parameters. The administration of antioxidants during cryopreservation is promised to have beneficial impacts on cryopreserved semen. Objective This review focused on discussing the beneficial impacts of antioxidant supplementation in human sperm cryopreservation. Methods We conducted a scoping review by the recommendations of the Joanna Briggs Institute and the Systematic Reviews and Meta- Analyses Extension for Scoping Reviews (PRISMA-ScR). This review focused on discussing the beneficial impacts of antioxidant supplementation in human sperm cryopreservation. Results From 444 records, 17 articles have been selected and extracted from four databases: Wiley, Ebsco, PubMed, and ScienceDirect. Conclusion The results indicated that the use of antioxidants, including both natural and synthetic ones, provides beneficial effects and better reproductive results for cryopreserved human sperm.BJMS, Vol. 25 No. 02 April’26 Page: 446-458